Direct percutaneous sac injection for postoperative endoleak treatment after endovascular aortic aneurysm repair - Uthoff, Heiko; Geisbüsch, Philipp (Journal of vascular surgery, 2012)
Background - This study presents the short-term and midterm results of direct percutaneous sac injection (DPSI) for postoperative endoleak treatment after endovascular aortic aneurysm repair (EVAR). - Methods - Between March 1994 and November 2011, EVAR was performed in 986 patients. The median follow-up was 63 ± 45 months (range, 0-211 months). A retrospective analysis was performed. DPSI was used in 21 patients for 19 type II endoleaks and two endoleaks of undefined origin (EOUO), of which 12 (57%) were after failure of a previous endovascular treatment attempt. - Results - DPSI using thrombin (n = 16), coils (n = 7), gelfoam (n = 6), or glue (n = 3), or a combination, was technically feasible in all patients. Saccography during DPSI revealed a previously undetected type I endoleak in three patients. Immediate DPSI success was achieved in 16 of 18 procedures (88.9%), with two complications. Glue incidentally intravasated in the inferior vena cava, causing a clinically nonsignificant subsegmental pulmonary artery embolism in one patient, and the temporary development of a type III endoleak, possibly from graft puncture, in another. During a median follow-up of 39 months (interquartile range, 13-88 months) after DPSI, recurrent endoleaks were observed in nine patients (50.0%), one type I endoleak due to graft migration, five type II endoleaks, and three EOUO. The occurrence of a re-endoleak during follow-up was significantly associated with dual-antiplatelet medication (0% in patients without re-endoleak vs 44.4% in patients with re-endoleak; P = .023) and with a nonsignificant trend for the use of aspirin alone (33.3% in patients without re-endoleak vs 80% in patients with re-endoleak; P = .094). Re-endoleak occurred in 33.3% of the patients without antiplatelet medication and in 100% of patients with dual-antiplatelet medication (P = .026). Thrombin was used as the sole embolic agent during the initial DPSI in all patients with dual-antiplatelet therapy. No other factor was significantly associated with re-endoleaks. Reintervention was deemed necessary in six patients within a median of 10 months (interquartile range, 4-16 months) after DPSI, including six additional DPSI treatments in four patients with type II re-endoleaks, cuff placements in one type I endoleak, and endograft relining in one EOUO. - Conclusions - This initial experience suggests that DPSI is feasible as a technique for endoleak treatment after EVAR. However, complications and endoleak recurrence remain a concern. The role of antiplatelet therapy and different embolic agents on long-term embolization success needs to be studied in more detail.